IMPLEMENTATION OF SUPPLY CHAIN MANAGEMENT IN MANAGING VEHICLE SPARE PARTS USING CODEIGNITER FRAMEWORK - Nurdian, Risky Agung; Zamakhsyari, Fardan; Amrozi, Yusuf (Politeknik Negeri Madiun, 2020)
Company Z is a business entity engaged in the distribution of motorcycle parts in partnership with local shops in the supply chain. The process of recording parts distribution services, service returns and report services is still done manually. So this process is quite vulnerable to data loss that has been recorded. Therefore, a more effective and efficient recording system is needed. The system will be designed using the concept of Supply Chain Management which includes the process of purchasing goods, selling goods, managing suppliers, returning goods and managing reports. In this study the authors used a descriptive qualitative research method with interview, observation and document collection data collection techniques. The system is designed using a codeigniter framework and uses a MySQL database. The system that has been designed can provide solutions in recording the purchase, sales, management, product returns, and report management services that have been carried out based on the website so that it becomes more effective and efficient.